New species of chitons of the superfamily Cryptoplacoidea (Mollusca: Polyplacophora) from Vietnamese waters - Sirenko, Boris I.; Saito, Hiroshi (Zootaxa, 2017)
Twelve species of the polyplacophoran genera Notoplax, Leptoplax, Acanthochitona and Cryptoplax (Chitonida: Acanthochitonina: Cryptoplacoidea) were found in Vietnamese waters for the first time. Five of them, namely Notoplax conica, Leptoplax doederleini, Leptoplax richardi n. comb., Acanthochitona achates and A. biformis, are new to Vietnamese fauna. The remaining seven species are new to science, namely: Notoplax odysseyi n. sp., Leptoplax nhatrangi n. sp., L. tongkingi n. sp., Acanthochitona condaoi n. sp., A. lanae n. sp., A. nigra n. sp. and A.ostreaphila n. sp. Leptoplax richardi n. comb. was transferred from the original genus Notoplax based on the redefinition of the genus given herein. We confirmed the occurrences of 21 species of the superfamily Cryptoplacoidea in the Vietnamese fauna, which makes them the richest group of chitons in Vietnamese waters. A peculiar feature, a comb-like blade in the major uncinal teeth of the radula is found in two new species, L. tongkingi n. sp. and A. ostreaphila n. sp. A similar feature is known only in two other distinct groups: the genus Ferreiraella of the family Ferreiraellidae of the order Lepidopleurida and the genera Tonicella and Boreochiton of the family Tonicellidae of the order Chitonida. This is the first report of this feature other than those two groups.